Analisis Nilai Kognitif Ritual Mosehe Wonua Sebagai Model Adaptasi Budaya Masyarakat Mekongga Di Kelurahan Wundulako - Komang Wahyu Rustiani; Alias Alias; Salniwati Salniwati; Abdul Rahman (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Human life is always under the influence of its culture. Although it is realized that culture is a product of humans in interacting with the environment and nature. However, the existence of culture is one of the fundamental aspects of human life in building their civilization. A culture that is continuously maintained always has cognitive value in it. Therefore, it is important to study the cognitive value of Mosehe Wonua as a cultural form of the Wundulako people. The purpose of this study was to analyze the cognitive value of the Mosehe Wonua ritual as a cultural adaptation model for the Mekongga community in Wundulako District. The method used in this research is descriptive qualitative with data collection techniques using three ways, namely interviews, observation, and document study. Based on the research results, it is known that the existing traditions and culture include the mosehe wonua ritual ceremony as an effort to purify the village / country in order to avoid catastrophe and disease outbreaks. The mosehe wonua ritual ceremony plays an important role in the life of the Mekongga ethnic community in Wundulako Village, Wundulako District, Kolaka Regency. The mosehe wonua ritual ceremony which the Mekongga community carries out every year has several cognitive values, namely: 1) cognitive values ​​as the principle of community religiosity, 2) cognitive values ​​as a medium for character education, 3) cognitive values ​​as the identity of the Mekongga community, and 4) cognitive values ​​as media of community cooperation. These values ​​are used by the Mekongga community in Wundulako as a unit when there are conflicts and conflicts. On the other hand, the mosehe wonua ritual is also used as a ritual to repel reinforcements such as during disease outbreaks or natural disasters